Simple repeated sequences in human satellite DNA. - Frommer, M (1982)
In an extensive analysis, using a range of restriction endonucleases, HinfI and TaqI were found to differentiate satellites I, II and III & IV. Satellite I is resistant to digestion by TaqI, but is cleaved by HinfI to yield three major fragments of approximate size 770, 850 and 950bp, associated in a single length of DNA. The 770bp fragment contains recognition sites for a number of other enzymes, whereas the 850 and 950bp fragments are "silent" by restriction enzyme analysis. Satellite II is digested by HinfI into a large number of very small (10-80bp) fragments, many of which also contain TaqI sites. A proportion of the HinfI sites in satellite II have the sequence 5'GA(GC)TC. The HinfI digestion products of satellites III and IV form a complete ladder, stretching from 15bp or less to more than 250bp, with adjacent multimers separated by an increment of 5bp. The ladder fragments do not contain TaqI sites and all HinfI sites have the sequence 5'GA(AT)TC. Three fragments from the HinfI ladder of satellite III have been sequenced, and all consist of a tandemly repeated 5bp sequence, 5'TTCCA, with a non-repeated, G+C rich sequence, 9bp in length, at the 3' end.